Mapping out halal certification in Indonesia and Malaysia: challenges, opportunities, and comparative advantage - Tohe, Achmad; Kholisin, Kholisin; Dariyadi, Moch Wahib; Omar, Noritah (Universitas Negeri Malang, 2021)
This study sought to map out the institutions and processes of halal certification in Indonesia and Malaysia by investigating the history, procedures, challenges, and opportunities. Data were gathered through interviews with those working in halal certifying related institutions, such as MUI and BPJPH in Indonesia, and JAKIM in Malaysia, in addition to several halal auditors from universities in both countries. A close reading of primary documents issued by halal certification institutions and secondary documents, academic articles, and online resources was conducted to better understand the issues at hand. The results suggest that while historically halal certification in Indonesia and Malaysia came from two different trajectories, the two finally converged in acknowledging the important role of the state and government in terms of Muslim consumer protection in relation to their halal needs. Nonetheless, their differing evolutionary paths, which was partly the function of the relative status of Islam in both, had eventually shaped the character of their halal certification. Originating from an organic civil society movement, halal certification in Indonesia traversed through a more stable and culturally consolidated process, while in Malaysia, it took the political highway with its attendant ups and downs. If Indonesia managed to create “umbrella halal law” overseeing other lesser provisions, Malaysia had to accept the fact that federation had some imprint on its vast array of dispersing halal provisions, if often compensated with some mending for improvement. Finally, the character and size of the population of each contributed to making Indonesia be more inward-looking and Malaysia outward-looking in their halal certification management.